Whole genome mRNA expression profiling revealed multiple deregulated pathways in stromal vascular fraction from erectile dysfunction patients. Issue 6 (23rd November 2018) - Vishnubalaji, Radhakrishnan; Manikandan, Muthurangan; Aldahmash, Abdullah; AlJarbou, Abdullah; Habous, Mohamad; Alhajeri, Dulaim; Almannie, Raed; Alfayez, Musaad; Alajez, Nehad M.; Binsaleh, Saleh
Abstract : Background: Stem-cell-based therapies have recently been explored in the field of erectile dysfunction (ED). However, the cellular and molecular phenotype of adipose derived stem cells (ADSCs) stromal vascular fraction (SVF) from ED patients remains largely unknown. Herein we compared the global gene expression profile in the SVF from ED patients and healthy individuals and identified altered signaling pathways between the two groups. Methods: Samples (2–5 g) of abdominal adipose tissue from ED patients ( n = 6) and healthy individual controls ( n = 3) undergoing elective cosmetic liposuction were collected. Immediately after removal, SVF was separated using Collagenase type I and type IV protocol. RNA was isolated and microarray experiments were conducted using the Agilent platform. Data were normalized and pathway analyses were performed using GeneSpring software. Results: Our data revealed multiple differentially expressed genes between the ED and control group. Hierarchical clustering based on differentially expressed mRNAs revealed clear separation of the two groups. The distribution of the top enriched pathways for the up-regulated genes indicated enrichment in inflammatory response and T-cell receptor signaling, while pathway analysis performed on the down-regulated genes revealed enrichment in mitogen-activated protein kinase, TGF-β, senescence, FAK, adipogenesis, androgen receptor, and EGF–EGFR signaling pathways in SVF from ED patient. Conclusion: Our data revealed the existence of multiple altered signaling pathways in the SVF from ED patients, which could potentially play a role in the etiology of this disease. Therefore, therapeutic strategies targeting these pathways might provide novel therapeutic opportunity for ED patients.